Mapping Digital Forensics and Crime: A Scholarly Overview - Dewi, Citra Surya; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This data article offers a comprehensive scholarly overview of the digital forensics and crime research landscape from 2002 to 2012, as captured from Lens.org. Employing the search terms "Digital Forensic" and "Crime," we identified a corpus of 2,078 documents. The research's primary objectives were to provide insights into the abundance of research articles in this intersection and to facilitate future explorations in digital forensics and crime. Data filtering encompassed document type, date range, and subject matter (Law), yielding a final dataset of 41 journal articles. The results revealed trends in institutional contributions, active authors, leading fields of study, prominent publications, and the most prolific publishers. This dataset will empower researchers, students, and practitioners embarking on digital forensic investigations and studies of cybercrimes. Highlight: Comprehensive Dataset: A robust dataset comprising 2,078 scholarly publications related to digital forensics and crime was assembled from 2002 to 2012. Research Insights: The data analysis sheds light on active institutions, prolific authors, dominant research fields, significant publications, and prominent publishers in this domain. Valuable Resource: This dataset serves as a valuable resource for researchers, students, and practitioners interested in exploring the intersection of digital forensics and crime, providing insights into research trends and key contributors. Keywords: Digital Forensic, Crime, Scholarly Publications, Data Analysis, Research Trends.